2020
DOI: 10.1371/journal.pone.0230005
|View full text |Cite
|
Sign up to set email alerts
|

Real world clinical practice in treating advanced hepatocellular carcinoma: When East meets West

Abstract: Background and aims The Barcelona Clinic Liver Cancer (BCLC) stage C (BCLC C) of hepatocellular carcinoma (HCC) includes a heterogeneous population for which sorafeninb is one of the recommended therapies. We aim to evaluate the real world clinical treatment and survival of BCLC stage C patients in an Asian cohort. Methods This is a retrospective cohort study that enrolled 427 consecutive BCLC stage C patients diagnosed between 2011 and 2017 by using the HCC registry data for our hospital. All patients were ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The EASL guidelines recommend that LR only be considered for minor branch PVTT of HCC (Vp1 or Vp2) [ 6 ]. At the investigated hospital, LR can be considered for PVTT limited to the first-order branch (Vp3) [ 29 ], and the outcomes are acceptable, as reported in our previous study [ 34 ]. A significant proportion of the patients with stage C HCC in this study underwent other treatments because sorafenib was reimbursed for selected stage C patients.…”
Section: Discussionmentioning
confidence: 94%
“…The EASL guidelines recommend that LR only be considered for minor branch PVTT of HCC (Vp1 or Vp2) [ 6 ]. At the investigated hospital, LR can be considered for PVTT limited to the first-order branch (Vp3) [ 29 ], and the outcomes are acceptable, as reported in our previous study [ 34 ]. A significant proportion of the patients with stage C HCC in this study underwent other treatments because sorafenib was reimbursed for selected stage C patients.…”
Section: Discussionmentioning
confidence: 94%
“…Retrospective studies focusing on patients with PVT have revealed that patients receiving HAIC had a longer OS compared with those receiving sorafenib treatment [ 22 , 28 ]. HAIC also provided survival benefits for large HCC as shown in retrospective studies [ 32 , 33 ], and also in a randomized Phase 3 study comparing HAIC and TACE in large (>7 cm) intermediate HCC [ 34 ]. Adverse events of HAIC in these studies were relatively low [ 32 , 34 ].…”
Section: Haic Monotherapymentioning
confidence: 99%
“…Several recent studies, however, have suggested that patients with symptomatic HCC without MVI or EHS should not be regarded as having advanced-stage disease. Furthermore, patients with advanced HCC without MVI or EHS in a real-world setting have frequently been treated with locoregional therapy, such as transarterial chemoembolization (TACE) (6)(7)(8)(9)(10). The efficacy of TACE, however, has been insufficiently defined, and factors associated with prognosis in patients treated with TACE remain unclear.…”
Section: Introductionmentioning
confidence: 99%